MEMFASILITASI ORANG TUA MURID MELALUI KOMUNIKASI VISUAL TENTANG MULTIPLE INTELLIGENCE DI SD ‘X’ TANGERANG - Hartini Laswandi; Heni Mularsih (Jurnal Bakti Masyarakat Indonesia, 2020)
The availability of a facility in the form of infographic or visual communication in a school, there will be a perception and understanding. The purpose of this research is to develop a visual or infographic communication design to provide students with parents' perceptions and understanding, teachers and school users about multiple intelligence. Previous research related to infographics such as the application of color, public service announcements, and the role of infographics as learning media. Methods using an ethnographic approach include examining participants' behavior in certain social situations and also understanding their interpretation of the behavior. Observations, literature studies, and ethnographic interviews were conducted for the data collection process. The data is the basis for designing information designs on posters and ex-banners that are able to provide information about multiple intelligence. The results of this research can provide solutions and benefits, (1) Infographic Design; the school understands that it is necessary to seek information visually about the abilities of students in utilizing multiple intelligence (Multiple Intelligence) that is quite important (2) Implementation of visual /infographic communication design or visual media, can provide information visually clearly . Such as posters, advertisements, leaflets and ex banner printing. In addition, this infographic (posters, leaflets and ex-banner printing) needs to be implemented to provide information services related to the ability of students to use Multiple Intelligence (Multiple Intelligence) for parents.ABSTRAK:Ketersediaan  suatu fasilitas yang berupa infografis atau komunikasi visual di suatu sekolah, maka akan terjadi persepsi dan pemahaman. Tujuan dari penelitian adalah mengembangkan desain komunikasi visual atau  infografis untuk memberikan persepsi dan pemehaman kepada orang tua murid, guru dan pengguna sekolah tentang kecerdasan majemuk (Multiple Intelligence). Penelitian sebelumnya terkait infografis seperti penerapan warna, iklan layanan masyarakat, dan peran infografis sebagai media pembelajaran. Metode dengan menggunakan pendekatan etnografi mencakup pemeriksaan perilaku peserta dalam situasi sosial tertentu dan juga memahami interpretasi mereka terhadap perilaku tersebut. Observasi, studi literatur, dan wawancara etnografi dilakukan untuk proses pengumpulan data. Data tersebut menjadi dasar dalam perancangan desain informasi pada poster dan ex-banner yang mampu memberikan informasi tentang kecerdasan majemuk (Multiple Intelligence). Hasil penelitian ini dapat memberikan solusi dan manfaat, yaitu (1) Desain Infografis; pihak sekolah paham bahwa perlu untuk mengupayakan informasi secara visual tentang kemampuan yang dimiliki peserta didik dalam memanfaatkan Inteligensi ganda (Multiple Intelligence) itu merupakan hal yang cukup penting  (2) Implementasi Desain komunikasi visual/infografis atau media visual, dapat memberikan  informasi secara visual dengan jelas. Seperti poster, iklan, leaflet dan ex banner printing. Selain itu perlu diimplementasikan infografis ini (poster, leaflet dan ex-banner printing) untuk memberikan layanan informasi yang berkaitan dengan kemampuan yang dimiliki peserta didik dalam memanfaatkan Inteligensi ganda (Multiple Intelligence) pada orang tua.